1996
DOI: 10.1021/ef950228l
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Stabilizers for Jet Fuels and Similar Hydrocarbon Mixtures. 1. Comparative Studies of Hydrogen Donors

Abstract: The results of a number of screening experiments are reported that were designed to seek hydrogen donor molecules that function as high-temperature stabilizers (i.e., >400 °C) in jet fuels and similar hydrocarbon mixtures. The most important conclusion of this work was that in the temperature range between 400 and 450 °C, 1,2,3,4-tetrahydroquinoline (THQ) was by far the best thermal stabilizer that we have discovered to date and significantly more effective than benzyl alcohol (BzOH), our previous benchmark.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 9 publications
0
73
0
Order By: Relevance
“…In general, radical formation can be stabilized by the aromatic ring of a molecule such as 1,2,4-trimethylbenzene, which enhances the stability of the molecule compared to alkanes [50]. For fuel conservation in the military aircraft sector, additives with high thermal stability show a similar radical stabilization [51][52][53]. Due to this enhanced stability of the C-C-bonding, dodecane is more reactive towards CPOX compared to 1,2,4-trimethylbenzene and is therefore consumed at a higher rate.…”
Section: Influence Of Aromatic and Sulfur Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, radical formation can be stabilized by the aromatic ring of a molecule such as 1,2,4-trimethylbenzene, which enhances the stability of the molecule compared to alkanes [50]. For fuel conservation in the military aircraft sector, additives with high thermal stability show a similar radical stabilization [51][52][53]. Due to this enhanced stability of the C-C-bonding, dodecane is more reactive towards CPOX compared to 1,2,4-trimethylbenzene and is therefore consumed at a higher rate.…”
Section: Influence Of Aromatic and Sulfur Contentmentioning
confidence: 99%
“…With a slower rate in steam reforming, there will be a higher by-product concentration at the catalyst outlet as a lower amount of the remaining hydrocarbons including reactants and by-products are consumed. stability show a similar radical stabilization [51][52][53]. Due to this enhanced stability of the C-C-bonding, dodecane is more reactive towards CPOX compared to 1,2,4-trimethylbenzene and is therefore consumed at a higher rate.…”
Section: Influence Of Aromatic and Sulfur Contentmentioning
confidence: 99%
“…It has a three dimensional structure with orthorhombic symmetry [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. These materials are characterized by a 1-dimensional channel system parallel to c-axis with elliptical 10-membered ring with pore dimension of 0.39 x 0.63 nm [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The magnesium substituted MAPO-11, which has the acidic version of AEL structure might exhibit shape-selective catalysis of methylation of naphthalene.…”
Section: Modification Of Zsm 5 Using Ironmentioning
confidence: 99%
“…The magnesium substituted MAPO-11, which has the acidic version of AEL structure might exhibit shape-selective catalysis of methylation of naphthalene. reduces the consumption of structure-directing agents, and involves minimization of waste disposal and reduction of reactor volume [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. The uniform crystals with smaller particle size and also improvement of catalytic activity can be obtained by this method .…”
Section: Modification Of Zsm 5 Using Ironmentioning
confidence: 99%
“…Previous studies at Pennsylvania State University have demonstrated that during the pyrolytic degradation of coal-and petroleumderived jet fuels, hydrogen transfer form hydrogen-donors, such as those present in coal-derived JP-8C jet fuel, could play an important role in suppressing thermal solid formation [10,14]. In previous papers [15][16][17][18], it has been reported that the formation of carbonaceous materials in jet fuel can be retarded by hydrogen donors such as tetrahydronaphthalene (THN), tetrahydroquinoline (THQ), and tetrahydronaphthol (THNol); and aromatic alcohol-type molecules such as benzyl alcohol and benzenedimethanol. More recent work at Pennsylvania State University has shown that THNol (especially the 1,2,3,4-isomer) and THN as well as benzyl alcohol are effective hydrogen donors for capping aliphatic radicals formed at temperatures > 400 °C while being transformed into relatively stable products [19].…”
Section: Introductionmentioning
confidence: 99%